Implementasi Urusan Administrasi Kurikulum di Madrasah Tsanawiyah Persiapan Negeri 4 Medan - Hanna Solihah Mashar; Makmur Syukri; Enny Nazrah Pulungan (STID Raudlatul Iman Sumenep, 2024)
Research on the Implementation of Curriculum Administration Affairs at Madrasah Tsanawiyah Negeri 4 Medan Preparation aims to find out (1) How is the program for implementing curriculum administration affairs on a daily, monthly, semiannual, and annual basis at Madrasah Tsanawiyah Negeri 4 Medan Preparation, (2) What are the inhibiting factors in the program for implementing curriculum administration affairs at Madarsah Tsanawiyah Negeri 4 Medan Preparation, (3) What are the solutions in overcoming obstacles in the program for implementing curriculum administration affairs at Madarsah Tsanawiyah Negeri 4 Medan Preparation. The method used is a qualitative research method through a descriptive approach using direct observation techniques, interviews and documentation. The subjects of this study were vice principals in the field of curriculum, and administrative heads and staff. Data analysis techniques using data reduction, data presentation and drawing conclusions. Assurance of the validity of the research data uses credibility testing, transferability testing, dependency testing and firmness testing. Penelitian Implementasi Urusan Administrasi Kurikulum di Madrasah Tsanawiyah Persiapan Negeri 4 Medan bertujuan untuk mengetahui (1) Bagaimana program pelaksanaan urusan administrasi kurikulum pada harian, mingguan, semester-an, dan tahunan di Madarsah Tsanawiyah Persiapan Negeri 4 Medan, (2) Apa faktor penghambat dalam program pelaksanaan urusan administrasi kurikulum di Madarsah Tsanawiyah Persiapan Negeri 4 Medan, (3) Bagaimana solusi dalam mengatasi hambatan dalam program pelaksanaan urusan administrasi kurikulum di Madarsah Tsanawiyah Persiapan Negeri 4 Medan. Adapun metode yang gunakan adalah metode penelitian kualitatif dengan melalui pendekatan deskriptif yang menggunakan teknik observasi secara langsung, wawancara dan dokumentasi. Adapun subjek penelitian ini adalah wakil kepala sekolah di bidang kurikulum, dan kepala dan staff tata usaha. Teknik analisis data menggunakan reduksi data, penyajian data dan penarikan kesimpulan. Penjamin keabsahan data penelitian menggunakan pengujian kredibilitas, pengujian keteralihan, pengujian ketergantungan dan pengujian ketegasan.